Soil–plant transfer of polychlorinated biphenyls in paddy fields - Chu, Shaogang; Cai, Meilin; Xu, Xiaobai (The Science of the total environment, 1999)
In a field experiment, the transfer of polychlorinated biphenyls (PCBs) from contaminated soil to rice was investigated. The results show that rice is not subject to significant bioconcentration of PCBs from the surrounding environmental system and the distribution of PCBs in the plant shows that the concentration series is leaves>husk>stalk>rice. It is suggested that root uptake/translocation is not the main pathway of PCB contamination of rice, while atmospheric deposition might be the main pathway of most PCBs from soil to rice. Principal component analysis was performed with the standardized relative abundance of PCBs in the samples and main pollution source. The congener pattern of PCBs in the plant samples is not similar to those in soil and in fish.